Extensive Genital Warts in Man Hampering Conjugal Life: A Case Report (Anwer Khan Modern Medical College Journal, 2020)
Genital warts, commonly known as condyloma acuminata, caused by the proliferation of squamous epithelial cells in the presence of sexually transmission of human papilloma Virus (HPV) infection. In human, HPV infection results in simple condyloma acuminatum, giant condyloma or Buschke-LÖwenstein tumour, and seldom penile carcinoma. There are several modalities of treatment options available for genital warts- medical and surgical, alone or in combination. Sometimes extensive genital warts represent a district entity resulting from HPV infection and require surgical management. We present the case of a 42-year-old male; rickshaw puller had multiple professional female sexual partners, who presented with extensive genital warts in penoscrotal region. Lesions were treated due to failure of medical management, by wide electrosurgical excision and rotation scrotal skin flapsAnwer Khan Modern Medical College Journal Vol. 11, No. 1: Jan 2020, P 82-85